Facile access to functional polyacrylates with dual stimuli response and tunable surface hydrophobicity. Issue 20 (5th May 2021) - Mohammad, Sk Arif; Dolui, Subrata; Kumar, Devendra; Mane, Shivshankar R.; Banerjee, Sanjib
Abstract : Well-defined functional polyacrylates with dual stimuli response and tunable surface hydrophobicity were synthesized via the recyclable Ni–Co alloy catalyzed reversible deactivation radical polymerization technique at ambient temperature. Abstract : Magnetically separable and reusable Ni–Co alloy nanoparticles were employed to achieve ambient temperature reversible deactivation radical polymerization (RDRP) of methyl acrylate (MA), for the first time, yielding well-defined PMA (at least up to 124 500 g mol −1 ) with a low dispersity ( Đ ≤ 1.20). The controlled polymerization character of RDRP of MA was confirmed from the linear semilogarithmic plot exhibiting pseudo first order kinetics, a linear increase of the molecular weight of the polymer with monomer conversion maintaining low Đ and the synthesis of PMAs of varying molecular weights from 2200 to 124 500 g mol −1 with low Đ . In addition, linear PMA-Br was used as a macroinitiator for the synthesis of several well-defined PMA- b -poly(M) block copolymers (where "M" stands for (2-dimethylamino)ethyl methacrylate (DMAEMA), tert -butyl methylacrylate (TBMA) and 2, 2, 3, 3, 4, 4, 5, 5-octafluoropentyl acrylate (OFPA)), with acceptable Đ s (≤ 1.24), demonstrating the high chain-end fidelity of the macroinitiator. The synthesized PMA- b -PDMAEMA demonstrated dual pH- and thermo-responsive properties. Upon hydrolysis, the synthesized PMA- b -PTBMA leads to the formation of unprecedented carboxylic acid-functionalized PMA derivatives. PMA- b -POFPA copolymers with varying OFPA mol% in the copolymer led to polymers with tunable surface hydrophobicity, as revealed by the water contact angle measurements.